PERANAN ROOM ATTENDANT DALAM UPAYA MENINGKATKAN PELAYANAN TERHADAP TAMU DI HOTEL GOLDEN VIEW - Jefri; Supardi; Arina Luthfini Lubis (JURNAL MEKAR, 2023)
As an effort to develop special tourist attractions in the hotel industry to increase tourist attractiveness in Batam City, in producing goods and services for the needs of tourists according to these tourism destinations. The hotel industry has broad categories within the field of tourism specifically in the field of tourism which include lodging, food and beverage services, event planning, amusement parks and travel. A guest room (Room) is an important thing in hospitality and is the thing most sought after by local and foreign tourists, therefore the role of a Room Attendant is so important in maintaining cleanliness and quality so as to improve service to guests at the Golden View Hotel. This research was conducted at the Golden View Hotel Batam using qualitative research methods. Data collection techniques were carried out by interviewing 5 informants who were housekeeping employees. The data analysis technique used is data reduction, data display and data verification.